P-216 Allied Health Professional Support in Pediatric Inflammatory Bowel Disease: A Survey from the Canadian Pediatric IBD Network. (February 2017) - El-Matary, Wael; Benchimol, Eric; Mack, David; Huynh, Hien; Critch, Jeff; Samson, Charles; Deslandres, Colette; Jacobson, Kevan; deBruyn, Jennifer; Carroll, Matthew; Wine, Eytan; Van Limbergen, Joahn; et al.
Abstract : Background: There are no clear evidence-based recommendations to suggest the volume or the size of required healthcare professional support in pediatric inflammatory bowel disease (IBD). We conducted a survey among academic pediatric IBD centers in Canada as a part of a quality improvement (QI) initiative to collect data on the availability of allied healthcare professional support. The aim was to assess current physician, nursing and allied healthcare professional support across Canadian pediatric tertiary-care centers. Methods: A self-administered questionnaire was designed and piloted to examine available resources in pediatric centers within the Canadian Children IBD Network. The survey evaluated the number of full time equivalent (FTE) physicians, nurses/physician assistants, dietitians, social workers, and clinical psychologists providing outpatient care for children with IBD. Ratios of health care provider (HCP) to IBD patient and median (with interquartile range [IQR]) numbers of HCPs were calculated. Results: Responses were received from physicians in 11 of 12 (92%) tertiary pediatric gastroenterology academic centers participating in the Network. Five (45%) of 11 sites had dedicated IBD physicians, where IBD care was provided by a portion of pediatric gastroenterologists. Overall, the ratio of IBD patients to physicians was 101:1, nurses/physician assistants was 338:1, dieticians 702:1, social workers 1468:1, and clinical psychologists was 2985:1. The median FTE of allied health professionals providing IBD care at each site was 1.0 (IQR 0.5–1.0) nurse, 0.5 (IQR 0.1–0.8) dietitian, 0.1 (IQR 0.02–0.4) social worker, 0.05 (IQR 0.0–0.3) clinical psychologists. The median wait time for a new IBD patient to be seen in a clinic was 2 (IQR 1–3) weeks, to be scoped was 3 (IQR 1.5–5) weeks, and to undergo magnetic resonance enterography was 12 (IQR 4–12) weeks. Conclusions: This Canadian national survey provided evidence on the current pediatric IBD workload and available support for ambulatory pediatric IBD care in Canada. Our next step will be to examine outcomes including patients' satisfaction across different centers to estimate if those centers with better resources including allied health support would have better outcomes.